Postmoderni premik in razvoj podeželja - Kos, Drago (Urbani izziv, 1998)
Economic changes do not have direct influence on the level of social integration. One of the basic characteristics of developed modern societies is the multiplication of fundamental development factors. From the social and spatial planning point of view this change means that development cannot be explained singularly. A review of the postmodernist shift in contemporary societies is followed by the case of Slovenia, where the importance of the countryside and guidelines for development projects and renewal of villages are emphasised.
Keywords: družbene spremembe; družbeni razvoj; družbeno planiranje; podeželje; prostorsko planiranje; rural area; spatial planning; vrednote